ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY FOR STUDYING DSSC ELECTROLYTES - Naimjonov Arslonbek Maxammadjon o`g`li, (TADQIQOTLAR, 2025)
Abstract. Dye-sensitized solar cells (DSSCs) rely critically on the electrolyte to regenerate the dye, transport redox species, and sustain charge-transfer at the counter electrode while limiting recombination at the photoanode interface. Electrochemical impedance spectroscopy (EIS) is one of the most informative nondestructive methods for  separating  bulk  electrolyte  transport  from  interfacial  kinetics  and diffusioncontrolled  processes  across  a  broad  frequency  window.  This  review consolidates the theoretical basis of impedance spectroscopy in forms directly usable for  DSSC  electrolyte  research,  with  emphasis  on  Nyquist/Bode  interpretation, constant-phase  behavior,  diffusion  impedance,  and  the  relationship  between  fitted parameters and physically meaningful electrolyte properties such as ionic conductivity, effective permittivity, diffusion coefficient, mobility, and charge-carrier concentration. We  provide  a  rigorous  and  practical  workflow  for  designing  EIS  experiments  in symmetric "dummy" cells and complete DSSCs under dark and illumination, highlight pitfalls related to non-stationarity and model non-uniqueness, and describe validation using  Kramers-Kronig  consistency  tests.  Representative  electrolyte  formulations-including  iodide/triiodide  liquid  electrolyte  and  gel  polymer  electrolytes  based  on PAN/EC/PC with iodide salts and ionic-liquid iodides, as well as polymer blends such as PVP/PMMA-are discussed to illustrate how composition and morphology impact impedance signatures. The review closes with reporting recommendations aimed at improving  reproducibility  and  comparability  across  studies,  enabling  EIS-guided electrolyte optimization toward higher efficiency and improved stability DSSCs [1,2].